(untitled) (Research, Society and Development, 2020)
Objective: this article aimed to promote a discussion about the paradox of the theory contrasting the practice of men’s health in nursing care today based on the scientific arsenal. Methodology: this is a theoretical-reflective article, with a methodological approach to reviewing the literature, which used as a guiding focus the implementation of the National Policy for Comprehensive Attention to Men’s Health and the subjects based on its applicability within the context of Nursing Care. Results: a total of 34 articles was obtained, of which only 26 met the pre-established criteria. As for the exclusion, 4 were not available in full, 2 were doctoral theses and 2 did not respond to the guiding topic. Regarding the databases, 16 were contained in LILACS, 3 in Medline and 7 in SciELO. Final considerations: it is thus understood that the study was able to establish a close relationship between the theory of the Comprehensive Care Policy for Men’s Health and the practical reality through reflection, in order to point out the flaws and challenges that still need to be faced by the body manager and professional team to attend this part so far from their rights before citizenship.